GAMBARAN FAKTOR YANG MEMPENGARUHI SUDUTSUDUT LUMBOSAKRAL PADA NYERI PUNGGUNG BAWAH - Anne Beatrice Handoko,* Bambang Satoto,* Hermina Sukmaningtyas,* Dwi Pudjonarko** (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION MEASUREMENT OF LUMBAR CURVATURE AND LUMBOSACRAL ANGLES ARE USEFUL IN ANALYZING BIOMECHANICS CHANGES OF LOW BACK PAIN A SIMPLE AND PRACTICAL WAY TO MEASURE LUMBAR CURVATURE AND LUMBOSACRAL ANGLES CAN BE DONE EASILY BY CONDUCTING LUMBOSACRAL XRAY